Peran Moderasi Kebijakan Dividen dalam Menjelaskan Keterkaitan Likuiditas, Struktur Modal dan Arus Kas Operasional terhadap Nilai Perusahaan - Fiqrah Maulani; Herry Achmad Buchory (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to comprehensively analyze the effect of liquidity, capital structure, and operating cash flow on firm value, with dividend policy acting as a moderating variable, in non-financial sector companies listed in the LQ45 index during the 2020–2024 period. Liquidity is measured using the Current Ratio (CR), capital structure is measured using the Debt to Equity Ratio (DER), operating cash flow is measured using Operating Cash Flow (OCF), and dividend policy is measured using the Dividend Payout Ratio (DPR). The research adopts a quantitative approach using panel data regression on a sample of 21 companies that consistently appeared in the LQ45 index during the observation period. The model testing process identified the Fixed Effect Model (FEM) as the best-fit model to estimate the relationship between variables. The results of the study reveal that both CR and DER have a significant positive effect on firm value, indicating that higher liquidity and optimal capital structure can enhance firm performance and market valuation. In contrast, OCF does not show a significant effect on firm value, suggesting that cash flow from operations alone may not be sufficient to influence market perceptions. Furthermore, dividend policy as a moderating variable does not strengthen or weaken the relationship between CR, DER, and OCF with firm value, implying that dividend distribution decisions are not perceived by investors as a determinant in this relationship.